Synthesis, antimicrobial and cytotoxicity evaluation of new cholesterol congeners - Aly, Mohamed Ramadan El Sayed; Saad, Hosam Ali; Abdel-Hafez, Shams Hashim (Beilstein Journal of Organic Chemistry, 2015)
3β-Azidocholest-5-ene (3) and (3β)-3-(prop-2-yn-1-yloxy)cholest-5-ene (10) were prepared as substrates to synthesize a variety of three-motif pharmacophoric conjugates through CuAAC. Basically, these conjugates included cholesterol and 1,2,3-triazole moieties, while the third, the pharmacophore, was either a chalcone, a lipophilic residue or a carbohydrate tag. These compounds were successfully prepared in good yields and characterized by NMR, MS and IR spectroscopic techniques. Chalcone conjugate 6c showed the best antimicrobial activity, while the lactoside conjugate 27 showed the best cytotoxic effect in vitro.
Keywords: antimicrobial; chalcone; cholesterol; cytotoxicity; glycoside; triazole